Reconstruction of the abdominal wall: a case series - Kelson Kawamura; Igor Chaves Gomes Luna; Rafael Anlicoara; Priscila da Silva Lopes; Marcel Fernando Miranda Batista Lima (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Patients with abdominal wall defects present challenging complications that require the use of advanced surgical approaches. METHODS: This primary, retrospective, and descriptive study evaluated patients who underwent abdominal wall reconstruction at the Plastic Surgery Service of the Clinics Hospital of the Federal University of Pernambuco. RESULTS: The medical records of 18 patients were reviewed, including 15 women (83.3%) and 3 men (16.7%), with a mean age of 41 years (range, 16-79 years). Seventeen patients (94.4%) had a history of previous surgery. The causes of abdominal injury were cesarean section in eight cases (44.4%), oncologic surgery in six (33.3%), trauma surgery in two (11.1%), and bariatric surgery in two (11.1%). The etiology of the defect was necrotizing fasciitis in eight cases (44.4%), incisional hernia in four (22.2%), trauma in two (11.1%), surgical wound dehiscence in two (11.1%), abdominal wall neoplasia in two (11.1%), and total thickness defect in one (5.5%). The surgical interventions included the component separation technique in seven cases (38.9%), simple VY advancement flap in six (33.3%), closure with abdominoplasty in three (16.7%), and tissue expander in two (11.1%). Four patients (22.2%) presented complications. CONCLUSIONS: Abdominal wall defects are challenging cases for plastic surgeons, as their treatment is difficult, but the results are satisfactory even in the most severe cases.